2017
DOI: 10.7241/ourd.20173.71
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of geriatric dermatoses at a Tertiary Care Teaching Hospital of South Rajasthan, India

Abstract: Background: Geriatric health care has assumed worldwide importance due to increase in the life expectancy during the last few decades. Aging skin has a marked susceptibility to dermatologic disorders due to the structural and physiologic changes that occur as a consequence of intrinsic and extrinsic aging. Aim: This study was aimed to evaluate the magnitude, pattern, contributory factors and systemic association of various dermatoses among geriatric population. Materials and Methods: Patients aged 60 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
5
5
0
Order By: Relevance
“…Papulosquamous disoders constituted (7%) in the study population out of which psoriasis was common and found in (4.33%) of study population. The incidence of papulosquamous disoders in present study is in concordance with the study of goyal et al 17 with incidence 4 %. In our study erythroderma is found in 8(2.67%) cases which is comparible with study of Chopra A et al 18 Among benign skin tumour seborrheic keratosis was the most common type seen in 28 cases (9.33%).…”
Section: Discussionsupporting
confidence: 93%
“…Papulosquamous disoders constituted (7%) in the study population out of which psoriasis was common and found in (4.33%) of study population. The incidence of papulosquamous disoders in present study is in concordance with the study of goyal et al 17 with incidence 4 %. In our study erythroderma is found in 8(2.67%) cases which is comparible with study of Chopra A et al 18 Among benign skin tumour seborrheic keratosis was the most common type seen in 28 cases (9.33%).…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of viral infection was comparable to study reported by Goyal et al 15 (10.6%). Herpes zoster (13 cases, 5.28%) and Post herpetic neuralgia (5 cases, 2%) which is a late se-qualae of Herpes zoster were the notable infection among viral infections.…”
Section: Discussionsupporting
confidence: 90%
“…This is largely in tune with other studies [10][11][12][13] . In a few studies females have outnumbered male patients [14][15] .…”
Section: Discussionmentioning
confidence: 99%